The effectiveness of positive psychological reinforcement in developing self-confidence of youth players (aged 10-14 years) at Football academy in Kurdistan Region of Iraq - Abdullah, Khaled Hussein (Sulaimani Journal for Humanities, 2023)
The research aims to build a program through psychological reinforcement to develop the trait of self-confidence among Academy school players. The researcher created a scale for the purpose of measuring this trait in order to measure the trait of self-confidence. The researcher did the extraction of honesty and stability and applied the scale to a sample of (251) players from the football Academies in the region, namely (Koye, Zakho, Erbil, Sulaymaniyah, Soran, Taqtaq). The researcher used the statistical package for the social sciences (SPSS) to analyze the data and extract the discriminatory power and internal consistency and extract stability by means of (Cronbach’s alpha)’s method. Following the completing of the making up of the scale, the researcher built a program in psychological reinforcement in order to develop the trait of self-confidence among football school players. The program was applied to a sample of football Academy in the district of Koye, and the number of players reached (20) players, and they were randomly divided into two groups: (10) players of the control group and (10) players of the experimental group. The proceeding and application of the program took two months, as (2) units per week, with a total of (12) units. The most important results were: -There are statistically significant differences between the pre- and posttests for the control and experimental groups -There are differences between the post-tests for the control and experimental groups. -The researcher concluded the research with a set of recommendations and suggestions based on the research results.
Keywords: positive psychological reinforcement; selfconfidence; football Academy players